Leptagrion jeromei (Odonata: Coenagrionidae) spec. nov. from Brazil, with notes on L. andromache Hagen in Selys, 1876 - Vilela, Diogo Silva [UNESP]; Garcia, Manoel Daltro Nunes Junior; Furieri, Karina S.; Lencioni, Frederico A A (Magnolia Press, 2021)
A new species of Leptagrion Selys, 1876 is described and named in honor to Dr. Jerome Constant: Leptagrion jeromei (Holotype: Brazil: Bahia, Jussari, RPPN Serra do Teimoso, Jequitiba tree (Cariniana legalis (Mart.) Kuntze, 1898) at 32 m, 10.v.2005, K.S. Furieri leg and deposited in FAAL). This species was confused for a long time with L. andromache Hagen in Selys, 1876 its closest congener. Diagnostic illustrations of L. andromache (lectotype and specimens collected at AmapBrazil) and L. jeromei spec. nov. are presented. We also present the northernmost record for L. andromache in Amap state, Northern Brazil.